A rare presentation of adult onset Still’s disease in an elderly patient (Rheumatology Reports, 2011)
Adult onset Still’s disease (AOSD) is a rare inflammatory disorder of unknown etiology that usually affects young adults. Very few patients older than 70-year-old have been reported. Clinical features include quotidian fevers, arthralgias, arthritis, pharyngitis, lymphadenopathy and an evanescent rash. AOSD should be considered in the differential diagnosis of fever of unknown origin. Early diagnosis is often difficult since it is a diagnosis of exclusion and the presence of infectious, neoplastic and autoimmune conditions needs to be ruled out before the diagnosis is made. No specific laboratory tests are available to aid in the diagnosis of AOSD. As a result, a set of diagnostic criteria that define the clinical features of this condition, termed the Yamaguchi criteria, have been most commonly used to establish the diagnosis. We describe the case of a 72-year-old Caucasian male with past medical history significant for generalized anxiety disorder, depression, BPH, and hypertriglyceridemia, who presented to a tertiary institution complaining of profound generalized weakness and weight loss that started three weeks prior to presentation. Initial laboratory studies showed leukocytosis, elevated ESR, CRP, ferritin and liver dysfunction. Cultures, ANA and rheumatoid factor studies were negative. The patient underwent further extensive workup that excluded the presence of infectious, neoplastic and autoimmune disorders and was subsequently diagnosed with AOSD and new onset diabetes mellitus. For the management of AOSD he was started on prednisone with significant improvement in markers of inflammation, symptoms and level of function.